2017
DOI: 10.1016/j.beproc.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Occasion setting, inhibition, and the contextual control of extinction in Pavlovian and instrumental (operant) learning

Abstract: An occasion setter is a stimulus that modulates the ability of another stimulus to control behavior. A rich history of experimental investigation has identified several important properties that define occasion setters and the conditions that give rise to occasion setting. In this paper, we first consider the basic hallmarks of occasion setting in Pavlovian conditioning. We then review research that has examined the mechanisms underlying the crucial role of context in Pavlovian and instrumental extinction. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 91 publications
(154 reference statements)
4
105
1
Order By: Relevance
“…Extinguishing S1R1 and S2R2 individually (Experiment 1) revealed that R1 was weaker at the beginning of extinction in Context B than it was in Context A (Figure 6a). That result is consistent with our work with simple operants suggesting that operant behavior is weakened when the context is changed after conditioning (e.g., Bouton et al, 2011; Bouton, Todd, & León, 2014; Thrailkill & Bouton, 2015b; see Trask, Thrailkill, & Bouton, 2016 for further discussion). However, in the groups extinguished with S2R2, there was no effect of switching contexts from A to B (Figure 6b).…”
Section: Relapse Of Chained Behaviorssupporting
confidence: 91%
“…Extinguishing S1R1 and S2R2 individually (Experiment 1) revealed that R1 was weaker at the beginning of extinction in Context B than it was in Context A (Figure 6a). That result is consistent with our work with simple operants suggesting that operant behavior is weakened when the context is changed after conditioning (e.g., Bouton et al, 2011; Bouton, Todd, & León, 2014; Thrailkill & Bouton, 2015b; see Trask, Thrailkill, & Bouton, 2016 for further discussion). However, in the groups extinguished with S2R2, there was no effect of switching contexts from A to B (Figure 6b).…”
Section: Relapse Of Chained Behaviorssupporting
confidence: 91%
“…Research on the contextual control of instrumental behavior and extinction has also been directed at the behavioral mechanisms underlying contextual control (see Trask, Thrailkill, & Bouton, 2017, for a review). Several possibilities have been considered, and they are sketched in Figure 1 as they might occur in a simple free-operant situation (see also Bouton & Todd, 2014).…”
Section: Mechanisms Of Contextual Controlmentioning
confidence: 99%
“…While not approaching the cocaine cue (above), no explicit alternative behavioral response was available to GTs and, therefore, we did not observe any systematic behavior in GTs in lieu of approaching the cue. Given this top-down processing bias in GTs, we predicted that they should be robustly more capable than STs in the processing of a complex contextual cue, or occasion setter (Bueno & Holland, 2008; Crombag, Bossert, Koya, & Shaham, 2008; Trask, Thrailkill, & Bouton, 2017) that indicates the availability of drug but, in contrast to a Pavlovian cue, does not merely precede the delivery of drug to an otherwise passive animal. Moreover, the processing of such a contextual cue by GTs should depend on cholinergic mechanisms.…”
Section: Impact On Addiction: II In Gts Cholinergic Activity Is Necmentioning
confidence: 99%